Oral Rehydration Solution: An Appropriate Formula for Acute Infantile Diarrhoea - Sunoto Sunoto; Suharyono Suharyono; Suryono Wibowo; Wibowo Wibowo (Paediatrica Indonesiana, 1980)
A new formula of oral rehydration solution (kristalyte R) with the following composition: Na 51.2, K 25.0, C/ 37.5, Citrate 57.5 mEq/L, dextrose 100 and sucrose 52.0 mMol/L with the osmolality of 323 mOsm/L were tried in 21 acute infantile gastroenteritis with mild and moderate dehydration. The age of the patients varied from 2.5 to 36 months with the average of 13.4 months. As a control were used 21 children with the same age, same diagnosis and same nutritional state treated with oralyte with the composition of Na 90, K 15, Cl 75, HC03 30 mEq/L and glucose 120 mMol/L with the osmolality of 330 mOsm/L. Clinical observation and chemical observation were done before and after rehydration which usually occurred after 24 hours of treatment. Stool culture, W BC count and urinalysis were done on admission only. The results of the trial revealed that in kristalyte group better results were obtained in gaining the body weight, reducing the frequency of diarrhoea or fluid loss, acceptance of the solution and reducing the risk of periorbital oedema. No hypernatremia and neurological manifestations were found in both groups and all of the children were discharged on the third day in good condition.